The emerging Kuala Lumpur extended mega urban region (KLEMUR): implications on urban prosperity in Malaysia - Abdul Samad Hadi,; Shaharudin Idrus, (Penerbit Universiti Kebangsaan Malaysia, 2017)
About half century ago urban scholars in Malaysia described urban areas and towns in the country as ‘sleepy hollows’, functioning more as extractors of riches than creating wealth for the people and the economic growth of the Malay states. Today the Malaysian nation-state is having vibrant towns and cities promoting growth and modernity, and it begins to grapple with issues related to the rise of large urban regions. The largest is the urban region centering on the Kuala Lumpur city which in the last four decades has witnessed urbanized edges extending outwards in all directions. The relative weights of the region’s importance in the Malaysian urban landscape can be substantiated through a range of indicators including land use changes over time, social, economic, infrastructural and quality of life. The Kuala Lumpur mega urban region with extended urbanized areas on all sides of its border is the outcome of overlapping drivers that coalesce in time , beginning with the world integration of trade on spices in the 16th century, then the integration through colonial investments, trade, colonial intervention and administration, the present integration of the space-time through the globalization process leveraged on by the Malaysian nation-state for accelerating the socio-economic development of the people framed within the developmental state paradigm. Malaysian cities become a window of the rising prosperity. The fact that the KLEMUR is compressed in time and space, there are challenges which the article will discuss.